Does Compliance with Financial Fair Play Rules Improve the Football Clubs' Sport Performance and Their Chances to Reach UEFA Competitions? - Pedro Garcia-del-Barrio; Pablo Agnese (Institute of Labor Economics (IZA), 2021)
This paper evaluates the European football clubs' compliance with UEFA Financial Fair Play (FFP) regulations and the effect of financial stability on sport achievements. The empirical analysis uses data of teams competing in the 1st division of four top domestic leagues (Premier League, La Liga, Serie A, and Ligue 1) over the seasons 2009/10 to 2015/16. We control for team quality through the annual wages (in quadratic form) and use the Wage-to-Revenue (WRR) ratio as a proxy variable to measure how close the clubs meet the break-even requirements. Our results reveal that greater financial responsibility implies better sport performance and higher chances to qualify for the Champions and Europa Leagues.
Keywords: D22; J24; J33; 330; professional football; financial fair play; competitive balance; wage-to-revenue ratios